Management of Acute Respiratory Distress Syndrome (ARDS) patients: A Literature Review - Etika Emaliyawati; Hamidah Nurhalimah; Hesty Adha; Inas Shintia Balqis; Ismailah Alam; Michael Mochamad Danny; Novarina Ismayani Anumilah; Rahdatul Aisyiyah (Universitas Padjadjaran, 2021)
In general, Acute Respiratory Distress Syndrome or ARDS is acknowledged to be the cause of 10% opatients requiring ICU care, and about 3 million patients worldwide experience it. Despite the data, up to these days there haven’t been many treatments that are considered to be effective in preventing or treating ARDS.This research is a literature review with a narrative approach in which the researchers analyze several research articles. The present study aims to analyze the management of ARDS in reducing mortality, improving lung function and airway effectiveness. The articles were searched based on the publication year 2016-2020, with the keywords “Acute Respiratory Distress Syndrome” AND “Oxygen Saturation”, “Acute Respiratory Distress Syndrome” AND “Treatment”, “Acute Respiratory Distress Syndrome” AND “Management”; as well as the databases of PubMed, EBSCO and American Journal of Clinical Pathology.Based on the 14 articles selected using inclusion criteria, it was found that there were 8 treatments given to the ARDS patients to reduce mortality, namely Non-Invasive Ventilation (NIV), the use of corticosteroids, UC-MSC (umbilical cord mesenchymal stem cells), oxygen therapy, mechanical ventilation, HFNC, prone position, open lung approach (OLA), and simvastatin.Of the 8 analyzed treatments, 3 interventions were found to have the highest significance of improvement in lung function and quality improvement in several indicators such as decreased mortality rate, increased saturation, decreased hospitalization time, etc. These interventions were: (1) Non-Invasive Ventilation (p value <0.001); (2) simvastatin (p value <0.001); (3) Corticosteroid (methylprednisolone) (p value <0.001).